The drawn space for Autism Spectrum Disorder (ASD) - Pecora, Anna Lisa (Beyond accessibility. Cultural Heritage for All, 2023)
The research belongs to the disciplinary field of drawing disciplines, focusing attention on autism's needs, andaiming at guiding the architectural space perception using virtual reality. The drawing disciplines, providing aninterpretation of spatial syntax, become an interdisciplinary medium to observe with a new perspective the output data of the experimentation, this way incisively contributing to a field of research hitherto dominated only by medical, pedagogical, and technological disciplines. The interdisciplinary research methodologyintegrates the joint visions of multiple theoretical fields; in addition to the more specific one of drawing, alsothe ergonomic, pedagogical, museum sector and the neuroscience area. The author aims to fill some gaps,found in the investigated context, about human perceptual answers to the VR representation, shifting the focusof attention, from the technological aspects of the digital tool to the user. This way, the research increases thepotential of virtual reality as an educational and inclusive medium. Starting from these assumptions, the study deals with a profound analysis of the perceptive responses in the relationship between man and architecturalspace, both in the neurotypical context and in the autistic scenario, to explore the role of the drawings disciplineas a guide in the interpretation of spatial morphologies for people with perceptual impairments. Comparing theanalytical phase's output data, the research develops the main design objectives aimed at developing theguidelines tool for the autism-friendly virtual environment design. This way it overcomes the gaps of previousexperiments considering all the factors analyzed in the preliminary study phases, human and ergonomicfactors, perceptive, educational, and inclusive. The drawing disciplines, acting as an interdisciplinary medium,provide the most appropriate operational tools for achieving the preset objectives. The "re-design" of a spacecustomized to a weaker user's needs has, as a further consequence, the outcome of indiscriminately extendingthe possibility of access to culture, since improving the relationship with the space can also help improve our relationship with ourselves and with others.